DEMOKRASI DAN POLITIK MEDIA SOSIAL DARI ORDE BARU HINGGA REFORMASI - Qibthia, Maria (Fakultas Komunikasi, Sastra, dan Bahasa, 2014)
This paper discusses the influence of social media in leading democratiza-tion in Indonesia. By tracing two recent historical episodes; students? movement conducting the downfall of president Soeharto in 1998, and the role of social me-dia after Orde Baru as political usage, social media has many functions in lead-ing democratization. This paper also shows that social media plays the contest of power and image in political arena which I assumed as a tool of media politic, and control over the public sphere as one way in leading democratization